DSP Based Power Quality Analyzer using New Signal Processing Algorithms for Detection and Classification of Disturbances in a Single-phase Power System - Ramos, Pedro M. (2008)
This paper describes the prototype of a power quality analyzer designed for real-time detection and classification of disturbances that occur in a single-phase power system. The previously developed algorithm for disturbance detection and classification was improved and implemented in a standalone DSP based analyzer. Its performance was verified during long term monitoring of the power system.